2021
DOI: 10.1002/tie.22205
|View full text |Cite
|
Sign up to set email alerts
|

Launching new global products into subsidiary markets: The vital role of sales and marketing collaboration

Abstract: We examine how to encourage collaboration between local sales and marketing teams in multinational enterprise (MNE) subsidiaries in order to successfully commercialize new product launches by creating integrated, locally adapted implementation plans. Empirical research within six subsidiaries of an MNE operating in southern Latin America found that centrally produced processes alone were insufficient for successfully launching new products in these subsidiary markets. However, devolving power, while using cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In addition, recent studies in international business and marketing have identified that product, organizational and foreign market characteristics contribute to a firm's product strategy (Harvey and Griffith, 2007; Le Meunier-FitzHugh et al. , 2021; Rubera et al.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, recent studies in international business and marketing have identified that product, organizational and foreign market characteristics contribute to a firm's product strategy (Harvey and Griffith, 2007; Le Meunier-FitzHugh et al. , 2021; Rubera et al.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Consistent with contingency theory, we expect a direct relationship between the market environments in which a firm operates and its product strategy. The new product literature indicates that a product strategy varies depending on contingent variables in a dynamic environment (Harvey and Griffith, 2007; Le Meunier-FitzHugh et al. , 2021; Rubera et al.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations